Efforts to save savable marriage through reconciliation process under family law in Malaysia: Issues and challenges - Md Hashim, Noraini; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Ibrahim, Norliah; Rahmat, Nur Ezan; Abdul Syahid Sowell, Sarafuddin (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
It has been a trend in recent years that the divorce rate among Muslims and non-Muslims keep on increasing every year though the percentage slightly varies from group to the other. Divorce rate in Malaysia for both Muslims and non-Muslims had increased from 11.24% in 2001 to 18.67% in the year of 2010. This indicates that the rate of divorce among the married couples is on the rise every year in Malaysia. There are many reasons for the divorce which can be used by the couple as indication of intolerance and marriage breakdown. However, worst still the failure to make reconciliation effort as useful mechanism to resolve marital conflict contributes to the percentage of divorce. This is the scenario in Malaysian family law where the law relating reconciliation process is provided to amicably settle their dispute without going for divorce. However, it does not seem able to save marriages and application for divorce keeps on increasing year by year. Divorce should be the last option resorted to by a marriage couple in solving marital dispute and it should be chosen when there is a necessity for such. Divorce may negatively affecting the life of the couple and the children. To avoid from unnecessary divorce, this study analyse legal provisions, policies and practices on reconciliation process to settle dispute of marriage couple in Malaysia. Both laws applied for Muslim and non-Muslim will be reviewed in this study to identify the strength and weaknesses in these two jurisdiction. Beside the library research, interviews with the practitioners and couple who are involved in marital conflict will be conducted to understand the practical aspects and the issues faced by them in reconciling the marriage couple. It is hoped that this study and those earlier literatures on marriage reconciliation could shed lights to the question of effectiveness of current marriage reconciliation process and how it can be reformed for further improvement.